Antigone in Phoinissae or the large shadow of Sophocles' Antigone - Carmen Morenilla Talens (Humanitas, 2016)
Sophocles’ Antigone has influenced the transmission and the interpretation of Euripides’ The Phoenician Women. Three passages of The Phoenician Women have shown us an image of Antigone as quite human and as a brave woman closer to Sophocles’ Antigone. First the teichoskopia of the prologue; second, a central scene, lines 1264‑1283, prelude of the last stasimon; third, made by two scenes, lines 1480‑1539 and 1540‑1580, where the role of Antigone is remarkable and reveals her personality. The absence of the first, whose authenticity has been questioned, would deprive the Antigone shown in The Phoenician Women of some features that, as a whole, configure her character as being quite human.